Postoperative bleeding complications in breast conserving surgery and the role of antithrombotic medications: retrospective analysis of 4712 operations - Tamminen, Anselm; Aaltonen, Riitta I.; Ristola, Marko T. (BMC, 2026)
Background: This study aimed to evaluate the risk and timing of postoperative bleeding complications following breast-conserving surgery (BCS), with or without axillary surgery, especially in relation to perioperative management of antithrombotic medications.
Methods: Data from all patients who underwent BCS for breast cancer between 2010 and 2022 at a single university hospital were collected. Medical records were reviewed for reoperations, unplanned admissions, and patient characteristics.
Results: In total, 4712 breast-conserving surgeries and 3631 axillary surgeries were performed on 3838 patients. The risk of any bleeding complication was 1.1% (40/3571) in breast-conserving surgery, 0.3% (9/2847) in sentinel lymph node biopsy, and 0.5% (4/779) in axillary lymph node dissection. Upon arrival for treatment, 645 (17%) patients were taking antithrombotic medications. The risk of bleeding complications was not elevated in patients whose medication was discontinued at least a day before the surgery (OR 0.84, p = 0.76); but it was almost four-fold (OR 3.61, p = 0.026) in patients whose antithrombotic medication was continued. However, the absolute risk for bleeding complication was low in these patients as well (2.0%, 15/751). The majority of bleeding complications (85%, 47/55) occurred within 24 h after the surgery.
Conclusion: The risk for bleeding complications was elevated, but still low, after BCS with or without axillary surgery, when antithrombotic medications were continued through the surgical period. Discontinuing antithrombotic medications is not obligatory in these patients.